Dynamics of carbon storage in forage systems in a livestock farm in Concepción, Paraguay - Martínez-López, Roberto; Niz, Olga; Díaz-Lezcano, Maura; Centurión, Liz (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Although the capacity of plants to store carbon is known, obtaining information about the sequestration potential in the soil and in herbaceous, shrubby and tree biomass in land use systems is essential, even more in landscapes dominated by livestock. The objective was to study the dynamics of carbon storage in three different forage systems in a livestock farm in Concepción, Paraguay. For this, the carbon level was estimated at different soil depths (0-20, 20-40 and 40-60 cm) and in the herbaceous/shrub biomass in three systems (Brachiaria brizantha cv Marandú, Panicum maximum cv Colonial and Leucaena leucocephala consortium with colonial), with an interval of 30 days between the three measurement moments. The results generated from the biomass indicated that the system constituted by the colonial forage consortium with L. leucocephala, presented the highest level of carbon (3.73 t.ha-1), showing a significant difference in relation to the B. brizantha (2.12 t.ha-1; p<0.05). On the other hand, the initial period showed higher carbon concentration (4.55 t.ha-1; p<0.05). Likewise, a higher content was found at a depth of 0-20 cm (20.26 t.ha-1; p<0.05). These results were obtained in a winter process. In this regard, it is important to mention that forage shrubs in systems with pastures constitute a fundamental nutritional resource in winter, in this sense it is recommended to use improved and consortium pasture systems, to increase carbon storage, achieve stable and productive systems, in correspondence with its potentialities.